Network war as a form of contradictions escalation in modern society - Bankouskaya, Yuliya L. (Journal of the Belarusian State University. Sociology, 2023)
The purpose of the article is to study the phenomenon of network warfare, to identify its essential features. The need to clarify the specifics of this phenomenon is due to the diffuse ambivalence of the three main directions: creative and destructive trends in the development of the social system, regulatory and resource value aspirations of individuals and groups, positive and negative impact of conflicts on social processes. The reconstruction of the conceptual foundations of the network war contributes to clarifying the qualitative characteristics of modern society functioning, the specifics of whose existence is due to the increasing spread of network formations and the increase in their influence on all spheres of human activity. The heuristic potential of network structures socio-philosophical study is to identify their specific characteristics that affect the process of the deployment of contradictions, such as multichannel, openness, anonymity, de centralisation, physical distancing of actors, the mediated nature of their interaction, the possibility of rapid escalation of conflict, publicity, sensory reduction. Consideration of network structures as a complex, branched, multifunctional, multilevel and multivariate formation makes it possible to clarify the features of people’s conflict interaction. The increase in opportunities for manipulating the deeds and actions of both an individual and a social group, the focus on the formation of public opinion, the lack of reflection aimed at clarifying the essence of the existing problems, is a feature of human existence in the modern information and communication space.